2022
DOI: 10.1126/sciadv.abm4643
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid inhibitors mitigate vision loss in a mouse model of retinal degeneration

Abstract: Rod and cone photoreceptors degenerate in retinitis pigmentosa (RP). While downstream neurons survive, they undergo physiological changes, including accelerated spontaneous firing in retinal ganglion cells (RGCs). Retinoic acid (RA) is the molecular trigger of RGC hyperactivity, but whether this interferes with visual perception is unknown. Here, we show that inhibiting RA synthesis with disulfiram, a deterrent of human alcohol abuse, improves behavioral image detection in vision-impaired mice. In vivo Ca … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 64 publications
(88 reference statements)
2
16
0
Order By: Relevance
“…In addition, both GWAS and gene-based association analysis suggested CYP2C18 as a potential novel susceptibility gene for cluster headache. Interesting, CYP2C18 is a cytochrome P450 monooxygenase involved in retinoid metabolism [ 49 ], while retinoic acid is a molecular trigger of RGC hyperactivity [ 50 ]. Taken together, the top implicated genes in our study may modulate the function of RGCs; however, how this could be involved in cluster headache pathogenesis particularly circadian rhythmicity requires further validation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both GWAS and gene-based association analysis suggested CYP2C18 as a potential novel susceptibility gene for cluster headache. Interesting, CYP2C18 is a cytochrome P450 monooxygenase involved in retinoid metabolism [ 49 ], while retinoic acid is a molecular trigger of RGC hyperactivity [ 50 ]. Taken together, the top implicated genes in our study may modulate the function of RGCs; however, how this could be involved in cluster headache pathogenesis particularly circadian rhythmicity requires further validation.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, aberrant gap junction coupling maybe present in the outer retina, but gap junction coupling in the inner AII Amacrine On-Cone Bipolar cell (AII-CBC) network is likely unchanged (Borowska et al, 2011;Trenholm et al, 2012;Menzler et al, 2014). A few reports also support abnormal gap junction coupling between RGCs as a locus for spontaneous activity (Telias et al, 2019(Telias et al, , 2022Denlinger et al, 2020). To examine what changes may be involved in driving correlations in spontaneous activity, we first confirmed that spontaneous activity and synchronized activity are eliminated when gap junctions are blocked.…”
Section: Mutual Information As a Measure Of Redundant Informationmentioning
confidence: 77%
“…Briefly, aberrant gap junction coupling maybe present in the outer retina, but gap junction coupling in the inner AII Amacrine On-Cone Bipolar cell (AII-CBC) network is likely unchanged ( Borowska et al, 2011 ; Trenholm et al, 2012 ; Menzler et al, 2014 ). A few reports also support abnormal gap junction coupling between RGCs as a locus for spontaneous activity ( Telias et al, 2019 , 2022 ; Denlinger et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations